ENVIRONMENTAL TOBACCO SMOKE AS A CANDIDATE AGENT FOR CONSIDERATION BY THE DEVELOPMENTAL AND REPRODUCTIVE TOXICANT (DART) IDENTIFICATION COMMITTEE (Tufts Archival Research Center, 2007)
Report providing information on the possibility of tobacco smoke being added to a list of regulated carcinogens. Discusses the health effects of secondhand smoke and indicates the need for more information since exposure to secondhand smoke is quite large. Lists several studies confirming that tobacco smoke is quite dangerous. Concludes that it meets all criteria to be considered as an addition to the list.